Large area imaging of forensic evidence with MA-XRF. Issue 1 (December 2017) - Langstraat, Kirsten; Knijnenberg, Alwin; Edelman, Gerda; Merwe, Linda; Loon, Annelies; Dik, Joris; Asten, Arian
Abstract This study introduces the use of macroscopic X-ray fluorescence (MA-XRF) for the detection, classification and imaging of forensic traces over large object areas such as entire pieces of clothing and wall paneling. MA-XRF was sufficiently sensitive and selective to detect human biological traces like blood, semen, saliva, sweat and urine on fabric on the basis of Fe, Zn, K, Cl and Ca elemental signatures. With MA-XRF a new chemical contrast is introduced for human stain detection and this can provide a valuable alternative when the evidence item is challenging for conventional techniques. MA-XRF was also successfully employed for the chemical imaging and classification of gunshot residues (GSR). The full and non-invasive elemental mapping (Pb, Ba, Sr, K and Cl) of intact pieces of clothing allows for a detailed shooting incident reconstruction linking firearms and ammunition to point of impact and providing information on the shooting angle. In high resolution mode MA-XRF can even be used to provide information on the shooting order of different ammunition types. Finally, by using the surface penetration of X-rays we demonstrate that the lead signature of a bullet impact can be easily detected even if covered by multiple layers of wall paint or human blood.